Relationship of Land Cover Heterogeneity and Insecticide Use with Arthropod Community Structure in Rice Agroecosystems - Dewina, Restu Utari; Choesin, Devi N. (School of Life Sciences and Technology, Institut Teknologi Bandung, 2024)
Rice agroecosystems generally experience two kinds of environmental stresses, i.e., a decrease in the heterogeneity of land vegetation types due to the development of settlements in the border zone and the excessive use of insecticides. Both of these factors are known to affect the structure of the arthropod community in rice agroecosystems. However, studies related to the effects of these two stresses in shaping the structure of arthropod communities have not been widely carried out, especially during the planting period in the rainy season. This study aims toanalyze the relationship between land cover heterogeneity and insecticide use with the taxonomic and functional diversity of arthropods in thealpha, beta, and gamma dimensions. The study was conducted during the rainy season (October–March) on four rice agroecosystem sites in Bandung, West Java. Data was collected 30 and 50 days after planting (DAP). Arthropod samples were identified, and their taxonomic andfunctional diversity was calculated using the Shannon entropy formula (D). In general, land cover heterogeneity was positively correlated withthe value of arthropod taxonomic and functional diversity, especially in the early vegetative phase of rice plants (30 DAP). In con- trast,insecticides (g/m2) were negatively correlated with the value of arthropod diversity. The composition of arthropod species locally was relativelythe same except in the rice agroecosystem with the lowest land cover heterogeneity and the highest use of insecticides. Additionally, thecoefficient value of the insecticide variable has more influence on the value of arthropod diversity than the variable coefficient of land coverheterogeneity.